A novel approach to investigate delta phase precipitation in cold-rolled 718 alloys. (1st September 2018) - Low, Zi Kang; Chaise, Thibaut; Bardel, Didier; Cazottes, Sophie; Chaudet, Philippe; Perez, Michel; Nelias, Daniel
Abstract: This paper proposes a numerical alternative to the lengthy experimental approaches typically employed to characterize delta phase precipitation in 718 alloys. A high-throughput experimental case study is first performed on cold-rolled alloy 718 of known composition and initial microstructure. Direct resistance heating is used to generate highly heterogeneous thermal fields, which enables investigation of a wide range of temperatures with relatively few experiments. Through a coupled finite element and Kampmann-Wagner numerical model, topographies of delta phase characteristics resulting from the complex heat treatments are generated. The predicted precipitation state shows good agreement with scanning electron microscopy observations of the heat-treated samples, demonstrating the validity of the proposed numerical approach. Graphical abstract: Image 1